Command responsibility between personal culpability and objective liability: finding a proper role for command responsibility - Bonafè, Beatrice I. (Journal of international criminal justice, 2010)
This article examines the role that command responsibility currently plays in the case law of the International Criminal Tribunal for the former Yugoslavia (ICTY) and the International Criminal Tribunal for Rwanda (ICTR). The ad hoc tribunals rely in principle on a broad concept of command responsibility which can be applied to all superiors, including political and civilian ones. However, in practice, accused persons have only rarely been successfully charged under this form of liability. Indeed, recent case law has gradually adopted a rigorous approach with respect to the legal requirements of command responsibility. This has made it more difficult to establish criminal liability of superiors who have not directly participated in the commission of international offences. The ad hoc tribunals have expressed an explicit preference for forms of direct liability where the accused can be convicted both under direct and command responsibility. While the ICTY and ICTR have progressively interpreted other international legal concepts to deal effectively with collective crimes committed by leaders of organized groups, they seem to have confined command responsibility to international crimes perpetrated in typical military-like contexts